Pertanggungjawaban Pidana Wisatawan yang Merusak Cagar Budaya Uma Lengge Maria sebagai Upaya Menjaga Kelestarian Lingkungan Wisata di Desa Maria Kecamatan Wawo Kabupaten Bima - Lily Mirawaty; Andin Rusmini (PT. PENERBIT TIGA MUTIARA, 2023)
This research aims to analyze and evaluate the criminal liability imposed on tourists who damage the Uma Lengge Maria cultural heritage in Maria Village, Wawo District, Bima Regency. Bima is an area that has cultural and tourism diversity. One of the cultural and tourism diversity is the Uma Lengge Maria Cultural Reserve which is located in Maria Village, Wawo District, Bima Regency. Uma Lengge is a traditional house of the Bima people which has existed for a long time and must be maintained in its existence and beauty so that it remains intact and its beauty can be enjoyed for the future. This research use desciptive qualitative approach. A descriptive approach is an approach that aims to systematically describe the facts and characteristics of a particular population or in a particular field factually and carefully. Data collection methods were carried out by observation, interviews and documentation. The data analysis method is carried out in the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that legal action is taken against criminal liability for tourists who damage the cultural heritage at Uma Lengge Maria. Uma Lengge in the Maria Village Tourist Area, there are 13 uma lengge and 103 jompa. The existence of uma lengge must be maintained so that its existence remains well into the future. there are sanctions and criminal liability for tourists who damage the Uma Lengge Maria cultural heritage in Wawo District, Bima Regency, West Nusa Tenggara.